Demonstration of deep-space synchronous two-way laser ranging with a laser transponder aboard Hayabusa2. Issue 10 (15th May 2023) - Noda, Hirotomo; Senshu, Hiroki; Otsubo, Toshimichi; Takeuchi, Hiroshi; Courde, Clément; Kunimori, Hiroo; Moore, Christopher; Schreiber, Ulrich; Ogawa, Naoko; Saiki, Takanao; Takei, Yuto; Aimar, Mourad; et al.
Highlights: Synchronous two-way laser ranging in deep space was successful for the first time. A laser altimeter aboard spacecraft Hayabusa2 was used as an optical transponder. The longest distance was 6.46 million km. Abstract: In December 2020, synchronous two-way laser ranging in deep space was successful for the first time over distances up to 6.46 million km. A laser altimeter aboard spacecraft Hayabusa2 was used as an optical transponder, detecting laser pulses emitted from the ground stations on Earth and retransmitting the pulses from the spacecraft to the ground. These retransmitted pulses were successfully detected at the ground station. The experiment was conducted as a demonstration of the deep-space laser ranging. The repetition frequency of the onboard instrument was limited to 0.5 Hz, and there was a lot of background noise because the experiments were carried out in daytime on the ground. Nevertheless, laser detection on the ground was still possible due to the high time-correlation between the detected and the predicted in the presence of random noise. Procedures similar to satellite laser ranging were applied to create residuals by subtracting the orbit predictions of the spacecraft from the observed round-trip time. Furthermore, some of the transponder return pulses were uniquely identified, where the time coherence of the measurements had been recovered from the telemetry data of the laser altimeter.